Cranial osteopathy : principles and practice - Liem, Torsten; McPartland, John M.; Skinner, Evelyn; ScienceDirect eBooks (Edinburgh ; New York : Elsevier/Churchill Livingstone, 2004)
Cranial osteopathy is an increasingly popular treatment approach for many common disorders affecting the head and neck. This new clinical guide is the first and only in-depth resource on the subject, offering a comprehensive analysis of osteopathic dysfunctions and principles in the cranial field. It examines each cranial bone and describes its location, development, and clinical implications of dysfunction. This discussion is followed by guidance on inspection, palpation, biomechanical and biodynamical approach to the motility of each cranial bone, and explanations of appropriate intrasutural or intraosseal techniques. Excellent illustrations and step-by-step sequencing of techniques make this book an exceptionally valuable resource for clinical practice. Comprehensive approach offers in-depth coverage of the theory and practice of cranial osteopathy, as well as the anatomy and interrelationships of the structures involved. Logically organized, easy-to-follow chapters employ consistent headings for each structure and step-by-step sequencing of techniques. Extensive illustrations include high quality photographs and line drawings to clarify important concepts. The osteopathic methodology and treatment techniques are described for all cranial structures, including the osteopathic approach to headaches. A comprehensive chapter on the temporo mandibular joint includes detailed coverage of TMJ dysfunction and the osteopathic approach to treatment.
Forewords -- Acknowledgements -- Preface -- Acknowledgements -- Quotations -- Introduction -- 1. The sphenobasilar synchondrosis (SBS) -- 2. The ethmoid bone -- 3. Vomer -- 4. The Temporal bones -- 5. The Frontal bone -- 6. The Parietal bones -- 7. The Maxillae -- 8. The Palatine bones -- 9. The Zygomatic bones -- 10. The Nasal bones, lacrimal bones and inferior nasal conchae -- 11. The mandible and temperomandibular joint -- 12. The Orofacial structures, pterygopalatine ganglion and Pharynx -- 13. The Nasal cavity and paranasal sinuses -- 14. The Eye -- 15. The viscerocranium -- 16. Head, face and neck pain -- 17. The organ of hearing and balance -- 18. Midline -- 19. Special techniques -- 20. Biodynamic approach to cranial osteopathy -- Glossary -- German bibliography -- English reading list -- Index.
Includes bibliographical references and index.
Translated from the German.
Print version record.
Elsevier
Keywords: Osteopathic medicine -- Handbooks, manuals, etc; Skull -- Handbooks, manuals, etc; MEDICAL -- Pharmacology; Osteopathic medicine; Skull; Manipulation, Osteopathic -- methods; Head; Sacrum; Skull; Electronic books